Metabolômica, uma abordagem otimizada para exploração da biodiversidade brasileira: estado da arte, perspectivas e desafios - Cristiano Soleo Funari; Ian Castro-Gamboa; Alberto José Cavalheiro; Vanderlan da Silva Bolzani (Química Nova, 2013)
Brazilian biodiversity is a colossal source of secondary metabolites with remarkable structural features, which are valuable in further biodiscovery studies. In order to fully understand the relations and interactions of a living system with its surroundings, efforts in natural product chemistry are directed toward the challenge of detecting and identifying all the molecular components present in complex samples. It is plausible that this endeavor was born out of recent technological sophistication in secondary metabolite identification with sensitive spectroscopic instruments (MS and NMR) and higher resolving power of chromatographic systems, which allow a decrease in the amount of required sample and time to acquire data. Nevertheless, the escalation of data acquired in these analyses must be sorted with statistical and multi-way tools in order to select key information. Chromatography is also of paramount importance, more so when selected compounds need to be isolated for further investigation. However, in the course of pursuing a "greener" environment, new policies, with an aim to decrease the use of energy and solvents, are being developed and incorporated into analytical methods. Metabolomics could be an effective tool to answer questions on how living organisms in our huge biodiversity work and interact with their surroundings while also being strategic to the development of high value bio-derived products, such as phytotherapeutics and nutraceuticals. The incorporation of proper phytotherapeutics in the so-called Brazilian Unified Health System is considered an important factor for the urgent improvement and expansion of the Brazilian national health system. Furthermore, this approach could have a positive impact on the international interest toward scientific research developed in Brazil as well as the development of high value bio-derived products, which appear as an interesting economic opportunity in national and global markets. Thus, this study attempts to highlight the recent advances in analytical tools used in detection of secondary metabolites, which can be useful as bioproducts. It also emphasizes the potential avenues to be explored in Brazilian biodiversity, known for its rich chemical diversity.